Pengaruh Tingkat Ekonomi, Pengetahuan Administrasi Perpajakan, dan Kesadaran Wajib Pajak Terhadap Kepatuhan Pembayaran Pajak Bumi dan Bangunan (PBB) di Desa Selorejo Kecamatan Dau Kabupaten Malang - Ike Anita; Anik Malikah; Afifudin Afifudin (Universitas Islam Malang, 2023)
The purpose of this research is to determine the effect of economic level, tax administration knowledge, and taxpayer awareness on compliance with land and building tax payments in the Selorejo Village, Dau Sub-district, Malang City. The population of this research are all taxpayers in the Selorejo Village, Dau Sub-district, Malang City are 1.124 people. Sample calculation using the slovin formula and resulted in as many as 92 respondents. This research included in quantitative research. Source of data comes from primary data through questionnaires and interviews. The data analysis method that used are descriptive statistical analysis and multiple linear regression analysis. The result of the research show that simultaneously economic level, tax administration knowledge, and taxpayer awareness have a significant effect on compliance with land and building tax payments in the Selorejo Village, Dau Sub-district, Malang City. Partially, the economic level has no effect on compliance with land and building tax payments, while tax administration knowledge and taxpayer awareness has a positive effect on compliance with land and building tax payments in the Selorejo Village, Dau Sub-district, Malang City.Keywords : Land and building tax, compliance, economic level, tax administration knowledge, taxpayer awareness.